Sethian Luminaries in the Texts of Ritual Power and Related Coptic Compositions - Piwowarczyk, Przemysław (Gnosis, 2023)
Several texts of ritual power in Coptic contain the names of four spiritual powers known in the Sethian sources as luminaries. The article explores the relations between luminaries of the Nag Hammadi works and the “magical” and related texts. Two aspects are analysed. First, the sequence of luminaries, which is highly standardised in the Nag Hammadi Sethian dossier, and deviations from this standard in other texts help assess relations with original Sethian sources. Second, the texts of ritual power portray luminaries singing and playing musical instruments. The article traces the elements of the heavenly concert already in the Sethian texts. It also presents a development of this motif under the influence of the common Christian concept of the angelic concert in heaven.